Biochemical and Physical Signal Gradients in Hydrogels to Control Stem Cell Behavior. (25th August 2013) - Jeon, Oju; Alt, Daniel S.; Linderman, Stephen W.; Alsberg, Eben
<x xml:space="preserve">Abstract</x> Three‐dimensional (3D) gradients of biochemical and physical signals in macroscale degradable hydrogels are engineered that can regulate photoencapsulated human mesenchymal stem cell (hMSC) behavior. This simple, cytocompatible, and versatile gradient system may be a valuable tool for researchers in biomaterials science to control stem cell fate in 3D and guide tissue regeneration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>